2015
DOI: 10.1128/aem.00638-15
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal Pathogenic and Antimicrobial-Resistant Escherichia coli Contamination of 56 Public Restrooms in the Greater Minneapolis-St. Paul Metropolitan Area

Abstract: How extraintestinal pathogenic Escherichia coli (ExPEC) and antimicrobial-resistant E. coli disseminate through the population is undefined. We studied public restrooms for contamination with E. coli and ExPEC in relation to source and extensively characterized the E. coli isolates. For this, we cultured 1,120 environmental samples from 56 public restrooms in 33 establishments (obtained from 10 cities in the greater Minneapolis-St. Paul, MN, metropolitan area in 2003) for E. coli and compared ecological data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…Other humans who are colonized with ExPEC and phylogroup B2 strains undoubtedly are an important source for new acquisitions, since such strains are relatively common among healthy humans, and cohabiting individuals share intestinal E. coli strains extensively, suggesting that person-to-person transmission occurs (8)(9)(10)(11). Additionally, previous work, including studies by some of the present authors, identified ExPEC strains of potential human health relevance, including those from phylogroup B2, in diverse nonhuman reservoirs, such as retail food products (12,13), public restrooms (14), household pets (10,15,16), and environmental waterways (17)(18)(19). This supports the existence of environmental reservoirs of ExPEC.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Other humans who are colonized with ExPEC and phylogroup B2 strains undoubtedly are an important source for new acquisitions, since such strains are relatively common among healthy humans, and cohabiting individuals share intestinal E. coli strains extensively, suggesting that person-to-person transmission occurs (8)(9)(10)(11). Additionally, previous work, including studies by some of the present authors, identified ExPEC strains of potential human health relevance, including those from phylogroup B2, in diverse nonhuman reservoirs, such as retail food products (12,13), public restrooms (14), household pets (10,15,16), and environmental waterways (17)(18)(19). This supports the existence of environmental reservoirs of ExPEC.…”
mentioning
confidence: 57%
“…Consistent with the possibility that the present chicken and turkey source ExPEC isolates may represent APEC, they lacked sfa/foc, hlyD, and malX, as do many APEC strains, whereas many ExPEC strains from humans, cats, and dogs possess these traits b,c,d No. of isolates with indicated trait (column %) P value e Total (n ‫؍‬ 21) Goat (n ‫؍‬ 1) Cat (n ‫؍‬ 9) Dog (n ‫؍‬ 4) Horse (n ‫؍‬ 1) Chicken (n ‫؍‬ 1) Turkey (n ‫؍‬ 4) Pig (n ‫؍‬ 1) papG II 3 (14) 0 (0) 0 (0) 0 (0) 0 (0) 0 (0) 3 (75) 0 (0) 0.02 sfa/foc 14 papA, P fimbrial structural subunit (52%); papC, P fimbrial assembly (71%); papEF and papG, P fimbrial tip pilins and adhesin (57% each); papG I, variant P adhesin (11%); papG III, variant P adhesin (38%); sfaS, S fimbriae (5%); focG, F1C fimbriae (43%); iha, adhesin-siderophore (5%); fimA, type-1 fimbrial adhesin (100%); cnf1, cytotoxic necrotizing factor (48%); cdtB, cytolethal distending toxin B (24%); iroN, salmochelin receptor (86%); ireA, siderophore (29%); K1 capsule kpsM variant (10.5%); kpsMT III, group 3 capsule (5%); rfc, O4 lipopolysaccharide (11%); cvaC, colicin (microcin) V (24%); traT, serum resistance associated (43%); ibeA, invasion of brain endothelium (5%); ompT, outer membrane protease (71%); iss, increases serum survival (24%). d Traits sought but not detected: afa/draBC (Dr-binding adhesins), bmaE (M fimbriae), gafD (G fimbriae), K2/K100 kpsM variant, and fliC (H7 flagellar variant).…”
Section: Discussionmentioning
confidence: 99%
“…Beta-glucuronidase positive isolates will appear purple on Brilliance E. coli agar or dark-green on Petrifilm Select E. coli count plate. The use of chromogenic media is usually followed by analyses by other techniques, for example, PCR, PFGE, or sequencing [20].…”
Section: Convergence Of E Coli Isolatesmentioning
confidence: 99%
“…Isolation of E. coli for EXPEC detection can follow methods that have been mentioned previously for other pathotypes. Detection of EXPEC can be done by multiplex PCR targeting different genes some of which have been previously described and dot blot hybridization [1,20,27,28]. Typing of isolates from different sources can be done by different procedures including PFGE [20].…”
Section: Common E Coli Pathotypesmentioning
confidence: 99%
“…Therefore, the threat of antibiotic-resistance genes to public health may originate from public restrooms and sewage ( Mkrtchyan et al, 2013 ; Pepper et al, 2018 ; Hendriksen et al, 2019 ). Few studies have surveyed public restrooms for environmental ESBL-producing E. coli ( Mohamed et al, 2015 ). To better understand the burden of ESBL-producing or ceftriaxone-resistant E. coli and ST131 E. coli in public restrooms, we performed surveillance in public restrooms in southern Taiwan.…”
Section: Introductionmentioning
confidence: 99%